Hubungan Perilaku Caring Perawat Dengan Tingkat Kepuasan Pasien Di Rumah Sakit Umum Daerah Tanjungpura Tahun 2023 - Christo Khu; Alisarjuni Padang; Balqis Nurmauli Damanik (Journal Innovation In Education, 2023)
Providing nursing services based on nurses' caring behavior can improve the quality of health services. Nurses' caring behavior is not only able to increase patient satisfaction, but can also generate profits for the hospital. The aim of this research was to determine the relationship between nurses' caring behavior and the level of patient satisfaction in the Inpatient Room at Tanjungpura Regional Hospital. The research design used is a correlational design with a cross sectional approach. The sampling technique used was purposive sampling, namely 80 patients. Data analysis used the Spearman Rank Test with a Sig value of 0.001, where the value is < (0.05), which means that H0 is rejected and Ha is accepted. The correlation value shows 0.025, which means there is a strong relationship. It is recommended that nurses continue to develop caring behavioral abilities towards patients and improve skills and knowledge by increasing their education level and participating in training.